Augmentation of Enhanced HDR Utilizing Encoder to Estimate Yaw-Angle of Cleaning Robots. (7th March 2016) - Cho, Yoon Hee; Lee, Sang Cheol; Hong, Sung Kyung
This paper proposes an improved algorithm for augmenting the enhanced HDR by utilizing encoder readings to achieve further minimized drift on the yaw-angle estimation of cleaning robots. The primary idea of the proposed approach consists of two phases: 1) classifying the manoeuvre (stop, straight and curving) being carried out using logic as a function of encoder readings; 2) controlling the Attenuator gain, resetting the Binary I-controller and switching Integrator in the enhanced HDR structure, taking into account the identified manoeuvring conditions. The proposed algorithm is applied to a cleaning robot and the experimental data demonstrate the effectiveness of this approach.